Étude comparative de substances bioactives pour la protection des biens patrimoniaux contre les insectes ravageurs - Grazia Nicosia; Fabien Fohrer; Yoanna Dechezleprêtre; Virginia Gisel de Billerbeck (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Certain heritage collections get cyclically infested by pest insects. Currently used curative treatments are punctual eradication operations, but in no way do they prevent the chronic re-infestations of sensitive cultural objects. That is why certain repellent products are used preventively. But most of them have proved harmful to humans and many are about to be prohibited by European regulations and their national transcription. The use of essential oils, known for their effects on insects and their lower noxiousness, can be an interesting alternative. Consequently, the authors tested the repellent properties of a certain number of essential oils on Stegobium paniceum, an insect species found worldwide and broadly represented in heritage collections.